Dry weight loss in leaves of dominant species in a successional sequence of the Mesopotamian Espinal (Argentina) - Mendoza, Carlos A. (2017)
Aim of study: To compare litter decomposition dynamics among different species within a single forest type and also between a single species in different forest successional stages. Area of study: Different forests of a known successional sequence of the Mesopotamian Espinal, placed in Villaguay Department, Entre Ríos Province, Argentina. Material and methods: A standard “litter bags” technique was employed. Chemical analyses of C and N were performed for leaves. A regression analysis was applied and data were fitted to a double exponential model. Means estimated among forests and species within each forest were compared using the Tukey-Kramer test. Main results: The model predicted that leaves would completely mineralize in the mid-term. Leaf decomposition rate in different species (both in the Secondary forest and Mature forest) had dry matter residues in the following decreasing order: Acacia caven > Prosopis nigra > Prosopis affinis > Celtis ehrenbergiana. Research highlights: Successional stage was not found to be a factor determining the decomposition rate among species. Different decomposition rates, observed among different species, would not be attributed to initial quality of residues in terms of C and N, but would be associated with a positive feedback process related to nutrient cycle; thus, a greater decomposition would increase nutrient availability and, consequently, litterfall input.